Advocating Inoculation in the Eighteenth Century: Exemplarity and Quantification. Issue 2 (12th May 2016) - Eriksen, Anne
Argument: Smallpox inoculation was introduced in Europe in the early eighteenth century and has been considered the first mass treatment of disease based on practical use of probability calculations and mathematical tools of computation. The article argues that these new approaches were deeply entangled with other rationalities, most emphatically that of exemplarity. Changes in inoculation methods around mid-century gradually changed the conceptualization of disease, seeing all cases as fundamentally equal, and thus making it more relevant to count them. Arithmetic changed the ways of thinking about smallpox epidemics, but new ways of conceptualizing disease were vital to making it a matter of arithmetic at all. The article investigates what happened when numbers and figures were introduced into medical matters: Who did the figures really concern, and what types of argument were they fitted into? How were numbers transformed into metaphors, and how did quantitative argument work together with arguments from exemplarity?